The Relationship between Skin Diseases and Nutritional Deficiencies in Children - Nova Zairina Lubis; Fitriend Syahputri (Talenta Publisher, 2025)
Background: Nutritional deficiencies are a significant global health issue, particularly in children, as they can impair growth and development. The skin often reflects early signs of nutritional deficiencies, including macronutrient and micronutrient imbalances, which may manifest as specific dermatological symptoms. Early identification of these manifestations is crucial to prevent long-term morbidity and mortality. Aims: This review aims to explore the relationship between nutritional deficiencies and skin diseases in children, emphasizing clinical features, diagnostic approaches, and effective treatment strategies. Methods: A comprehensive literature review was conducted using relevant studies and case reports on pediatric dermatological manifestations caused by macronutrient and micronutrient deficiencies. Discussion: Nutritional deficiencies, including protein-energy malnutrition, essential fatty acid deficiency, and deficiencies of vitamins A, B-complex, C, and K, as well as zinc and copper, present with a wide range of skin manifestations. These include xerosis, dermatitis, hyperkeratosis, hyperpigmentation, and petechiae. Diagnosis involves a combination of dietary history, clinical examination, and laboratory tests to assess nutritional status. Treatment requires nutritional supplementation tailored to the specific deficiency, alongside supportive dermatological care. Conclusion: Dermatological manifestations are often the first indicators of nutritional deficiencies in children. Early recognition and a multidisciplinary approach to diagnosis and treatment are essential to improve outcomes. Future research should focus on integrating nutritional interventions with dermatological care to enhance recovery and prevent recurrence. Latar Belakang: Defisiensi nutrisi merupakan masalah kesehatan global yang signifikan, terutama pada anak-anak, karena dapat mengganggu pertumbuhan dan perkembangan. Kulit sering kali mencerminkan tanda-tanda awal defisiensi nutrisi, termasuk ketidakseimbangan makronutrien dan mikronutrien, yang dapat muncul sebagai gejala dermatologis spesifik. Identifikasi dini manifestasi ini sangat penting untuk mencegah morbiditas dan mortalitas jangka panjang. Tujuan: Tinjauan ini bertujuan untuk mengetahui hubungan antara defisiensi nutrisi dan penyakit kulit pada anak-anak, dengan melihat gambaran klinis, pendekatan diagnostik, dan strategi pengobatan yang efektif. Metode: Tinjauan literatur komprehensif dilakukan menggunakan studi dan laporan kasus yang relevan mengenai manifestasi dermatologis pada anak akibat defisiensi makronutrien dan mikronutrien. Diskusi: Defisiensi nutrisi, termasuk malnutrisi energi-protein, defisiensi asam lemak esensial, serta defisiensi vitamin A, B-kompleks, C, dan K, serta zinc dan tembaga, menunjukkan berbagai manifestasi kulit seperti xerosis, dermatitis, hiperkeratosis, hiperpigmentasi, dan petechiae. Diagnosis melibatkan kombinasi riwayat diet, pemeriksaan klinis, dan tes laboratorium untuk menilai status nutrisi. Pengobatan memerlukan suplementasi nutrisi yang disesuaikan dengan defisiensi spesifik, disertai perawatan dermatologis suportif. Kesimpulan: Manifestasi dermatologis sering kali menjadi indikator pertama defisiensi nutrisi pada anak-anak. Pengakuan dini dan pendekatan multidisiplin untuk diagnosis dan pengobatan sangat penting untuk meningkatkan hasil. Penelitian di masa depan perlu berfokus pada integrasi intervensi nutrisi dengan perawatan dermatologis untuk meningkatkan pemulihan dan mencegah kekambuhan.